PENGEMBANGAN MEDIA GAMBAR “ MYSTERY BOX READ ” BERBASIS KARAKTER UNTUK MENINGKATKAN KEMAMPUAN BACA TULIS SISWA DI SDN BEKTIHARJO VI DI KELAS 1 - Ervarisma Nur Aqqidahtul Izzah; Ina Agustin (ELENOR: Elementary School Journal, 2024)
The achievements in the development of the research aim to describe the development of media, the level of validity, practicality of the media, and the effectiveness of the media. This study uses a type of research and development (R&D) research. The ADDIE development model has 5 stages in the ADDIE model, including: 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluate. Data collection instruments use observation sheets, interview sheets, and expert validation sheets. Subjects of the character-based "Mystery Box Read" media trial to improve literacy Namely: Validation Experts 1) Material Experts, 2) Media Experts, 3) Linguists, 4) Teachers, 5) Students who are carried out at SDN BEKTIHARJO VI with a total of 10 students are specialized in grade 1 Indonesian Language Learning. The results obtained by the researcher to find out the level of media validity obtained very valid results from 3 validator assessments. The level of practicality was obtained from the questionnaire response of teachers and students obtained very practical results. To find out the level of effectiveness of students through student test sheets in the form of pre-test and post-test with a result of 9.48% calculated using the formula wardhana et al got the category of very effective. So that the "Mystery Box Read" media is character-based to improve students' literacy skills.